Analysis of Leadership Internal Control and Employee Commitment on Employee Performance - Ardiyanti, Effie; Nurwijayanti; Wardani, Ratna (Babali Nursing Research, 2023)
Introduction: Hospital is an organization or health institution that is responsible for the provision of health services ranging from basic and specialty medical services that are quality, effective, efficient, accountable and oriented to customer satisfaction. Hospitals which are places of health services must be able to provide professional resources. One way to improve the performance of employees, including nurses in hospitals, is to carry out good and directed supervision The purpose of the study was to determine the effect of leadership, internal control and employee commitment on employee performance at Gemolong Hospital. Methods: Observational research design with a cross-sectional approach. The population of all employees at Gemolong Hospital was 295 respondents. The sample was 170 respondents with proportional to size technique. The research measuring instrument used was a questionnaire, divided into 4 variables, leadership, internal control, commitment employee performance. The questionnaire that was carried out validity and reliability. Analysis used is univariate and multivariate analysis with linear regression using SPSS 23. Results: Linear regression tests conducted showed there was a relationship between leadership for the head of the room (p=0.007), leadership for the director (p=0.004), internal supervision (p=0.000) and employee commitment (p=0.011) to employee performance. Multivariate analysis showed that the influential variable was internal supervision with a significance level of p=0.000 and B=0.518. Conclusion: The research conducted are expected be input to the hospital to increase motivation and internal supervision to improve the quality of hospital services in the eyes of the community. Keywords: Leadership, Internal Control, Commitment, Performance